ADAR1 could be a potential diagnostic target for intrauterine infection patients - Keiichiro Nakamura; Kunitoshi Shigeyasu; Thuy Ha Vu; Jota Maki; Kazuhiro Okamoto; Hisashi Masuyama (Scientific Reports)
Abstract Intrauterine infection (IUI) is mainly an ascending infection in which vaginal and cervical pathogens ascend to the uterus and can affect the fetus. Until now, there is still no effective diagnostic biomarker for IUI, such as chorioamnionitis (CAM) and funisitis (FUN). Deoxyribonucleic acid (DNA)/Ribonucleic acid (RNA) editing molecules such as apolipoprotein-B mRNA-editing complex (APOBEC) 3 families and Adenosine deaminase family acting on RNA (ADAR)1 were examined in chorioamniotic membranes and umbilical cord of 83 patient samples. Furthermore, Ureaplasma parvum induced ADAR1 was investigated in human HTR-8/SVneo EVT cell line. ADAR1 had a significantly higher area under the curve (AUC) (0.721 and 0.745) than other APOBEC3s or cytokines in CAM and FUN patients. In vitro, ureaplasma parvum was demonstrated to activate ADAR1 (p = 0.025) and reduce RIG-I, IRF3, IFN- $$\:{\upalpha\:}$$ , and IFN-β expression in EVT cell line (p = 0.005, p = 0.010, p < 0.001, and p = 0.018, respectively). High expression of ADAR1 was strongly associated with CAM and FUN patients (multivariate analyses; p = 0.035 and p = 0.002). ADAR1 could be a potential diagnostic target for IUI, such as CAM and FUN patients.